The neuroprotective effect of vitamin E on waterpipe tobacco smoking-induced memory impairment: The antioxidative role - Alzoubi, Karem H.; Halboup, Abdulsalam M.; Alomari, Mahmoud M.; Khabour, Omar F. (Elsevier, 2019)
This study examined the neuroprotective effect of vitamin E against waterpipe tobacco smoking-induced memory impairment in rats. It investigated memory performance and oxidative stress biomarkers and reported that vitamin E prevented waterpipe smoking-induced memory impairment through antioxidative mechanisms.